Jim Crow, Jett Rink, and James Dean: Reconstructing Ferber’s Giant (1952-1956) - Smyth, J. E. (American Studies, 2007)
In the years since Giant’s release as a major Hollywood film, its complex portrait of the western hero and twentieth-century racism has been overshadowed by the legend of James Dean as one of America’s pre-eminent cultural icons. But ironically, Edna Ferber’s construction of the poor white ranch-hand, Jett Rink, and Dean’s performance are crucial in understanding Ferber and director George Stevens’ confrontation with the darker side of America’s frontier myths and Giant’s enduring racial legacy. This article examines Ferber and Stevens’ critique of postwar masculinity, the ideology of the western, and Texas racism within the context of Jett Rink’s transgressive racial hybridity.